Methyl Parathion Exposure Induces Development Toxicity and Cardiotoxicity in Zebrafish Embryos - Tianyi Chen; Haoze Chen; Anli Wang; Weixuan Yao; Zhongshi Xu; Binjie Wang; Jiye Wang; Yuanzhao Wu (Toxics, 2023)
Methyl parathion (MP) has been widely used as an organophosphorus pesticide for food preservation and pest management, resulting in its accumulation in the aquatic environment. However, the early developmental toxicity of MP to non-target species, especially aquatic vertebrates, has not been thoroughly investigated. In this study, zebrafish embryos were treated with 2.5, 5, or 10 mg/L of MP solution until 72 h post-fertilization (hpf). The results showed that MP exposure reduced spontaneous movement, hatching, and survival rates of zebrafish embryos and induced developmental abnormalities such as shortened body length, yolk edema, and spinal curvature. Notably, MP was found to induce cardiac abnormalities, including pericardial edema and decreased heart rate. Exposure to MP resulted in the accumulation of reactive oxygen species (ROS), decreased superoxide dismutase (SOD) activity, increased catalase (CAT) activity, elevated malondialdehyde (MDA) levels, and caused cardiac apoptosis in zebrafish embryos. Moreover, MP affected the transcription of cardiac development-related genes (vmhc, sox9b, nppa, tnnt2, bmp2b, bmp4) and apoptosis-related genes (p53, bax, bcl2). Astaxanthin could rescue MP-induced heart development defects by down-regulating oxidative stress. These findings suggest that MP induces cardiac developmental toxicity and provides additional evidence of MP toxicity to aquatic organisms.